Cost-effectiveness of next-generation vaccines: The case of pertussis. Issue 29 (17th June 2016) - Fitzpatrick, Meagan C.; Wenzel, Natasha S.; Scarpino, Samuel V.; Althouse, Benjamin M.; Atkins, Katherine E.; Galvani, Alison P.; Townsend, Jeffrey P.
Highlights: We develop the MCPI metric to quantify the value of improving an existing vaccine. The MCPI is the maximum cost-effective price increase for incremental improvements. We apply the MCPI to evaluate potential improvements in pertussis vaccines. It would be most valuable to extend the duration of the childhood series. Improvements to childhood series are most valuable, despite waning of adult boosters. Abstract: Despite steady vaccination coverage rates, pertussis incidence in the United States has continued to rise. This public health challenge has motivated calls for the development of a new vaccine with greater efficacy and duration of protection. Any next-generation vaccine would likely come at a higher cost, and must provide sufficient health benefits beyond those provided by the current vaccine in order to be deemed cost-effective. Using an age-structured transmission model of pertussis, we quantified the health and economic benefits of a next-generation vaccine that would enhance either the efficacy or duration of protection of the childhood series, the duration of the adult booster, or a combination. We developed a metric, the maximum cost-effective price increase (MCPI), to compare the potential value of such improvements. The MCPI estimates the per-dose price increase that would maintain the cost-effectiveness of pertussis vaccination. We evaluated the MCPI across a range of potential single and combined improvements to the pertussis vaccine. As an upper bound, we found that a next-generation vaccine which could achieve perfect efficacy for the childhood series would permit an MCPI of $18 per dose (95% CI: $12–$31). Pertussis vaccine improvements that extend the duration of protection to an average of 75 years would allow for an MCPI of $22 per dose for the childhood series (CI: $10–$33) or $12 for the adult booster (CI: $4–$18). Despite the short duration of the adult booster, improvements to the childhood series could be more valuable than improvements to the adult booster. Combining improvements in both efficacy and duration, a childhood series with perfect efficacy and average duration of 75 years would permit an MCPI of $39 per dose, the highest of any scenario evaluated. Our results highlight the utility of the MCPI metric in evaluating potential vaccines or other interventions when prices are unknown.